Jihad as A Realistic Approach: Responding to the Palestinian Colonization from 1948 to Present - aswar, Hasbi; Munzilin, Khairul (Islamic Research, 2025)
This article provides a new perspective on responding to the turmoil in Palestine from 1948 to the present. The main argument of this article is that the primary cause of the Palestinian issue is the existence of the Zionist Jewish occupiers in Palestinian land, supported by the United States and its allies. Hence, the solution to this occupation is to liberate Palestine from Zionist occupation. This study uses the concept of jihad in Islam as a framework to explain the steps in liberating Palestine. The method used is qualitative analysis of data collected from various books, journals, and websites. This study finds that, given the current conditions in Palestine, the approach of jihad is the most realistic approach that pro-Palestinian Muslim-majority countries can undertake. However, the implementation process is inaccessible due to several factors, including the political, economic, and military conditions in Muslim countries, as well as the dominant ideologies currently followed and applied by these countries.